ASPEK GEOLOGI LINGKUNGAN DALAM RANGKA PEMEKARAN WILAYAH ADMINISTRASI, DALAM PEMBANGUNAN IBU KOTA KABUPATEN BOGOR BARAT - Himmes Fitra Yuda; Muhammad Adimas Amri; Suherman Dwi Nuryana; Murni Sulastri; Novi Triany; Mohammad Apriniyadi; Syahadun Syahadun (Universitas Negeri Padang, 2023)
Disasters are events that can endanger life and disrupt people's lives. It can be caused by natural and non-natural factors, as well as those caused intentionally by humans, resulting in fatalities, property losses, natural and environmental damage, and psychological effects on disaster victims. Natural disasters themselves are a threat to the community and the Regent. The Rumpin District, Bogor Regency, as the capital of the candidate for the newly autonomous region of West Bogor Regency, has triggered population growth and the development of the area has become very fast. Deliberation of the potential and resources owned and assessed to be a strategic area because it borders the City of South Tangerang, Banten. Therefore, the activities of managing natural resources and the environment as well as regional development must pay attention to the preservation of their functions and capabilities so that development activities do not become a trigger for disasters, and the location of the development must be in an area that is safe from disasters. This study was conducted to find out how the geological conditions are related and the factors that affect the potential for landslides, and to make a map of the land movement susceptibility zone in the research area. This research uses Geographic Information System (GIS) and the parameter assessment method, where the parameters needed are geological parameters, soil type, rainfall, land use, and slope. The disaster risk zoning is expected to be a source of knowledge for the community and the city government of Bogor for disaster mitigation and increase awareness related to land movement vulnerability zones.